HD-SEIRS Malware Propagation Model in Heterogeneous Complex Networks - Elham Asadi; Soodeh Hosseini (مجله مدل سازی در مهندسی)
In recent years, the Internet has become part of the requirements of human life. With the widespread use of the Internet, the Web, and online social networks, the number of vulnerabilities and security threats has increased significantly. Various types of malwares (worms and viruses) have become a major threat to the security of systems and networks. In this regard, researchers are looking for ways to identify malware and fight against them. One of the methods used in this field is to model the malware propagation in order to identify and combat malware by modeling its behavior. In this article, a malware propagation model based on the propagation of epidemic diseases in a heterogeneous network structure, considering the devices connected to the network and the Internet, is introduced. Modeling is done based on the Susceptible-Exposed-Infected-Recovered epidemic model for devices and Internet networks. The results show that the speed of malware propagation in the proposed HD-SEIRS model is significantly reduced compared to the SEIR model. Also, in this article, the basic reproduction ratio (R_0 )  is calculated for the proposed model and the effect of parameter changes on the proposed model is investigated.